INTENSI BERWIRAUSAHA DITINJAU DARI EFIKASI DIRI DAN KREATIVITAS - Henry Anggoro Djohan (Universitas Kuningan, 2021)
This study aims to determine whether there is an effect of self-efficacy and creativity on entrepreneurial intentions, and the magnitude of the effect of self-efficacy and creativity both simultaneously on entrepreneurial intentions. This study uses a quantitative approach with multiple linear regression methods to test the hypothesis between the independent and dependent variables of the study. Samples were obtained from students of SMA Masehi 2 PSAK as many as 69 respondents. The results showed that self-efficacy and creativity had a positive and significant effect on students' entrepreneurial intentions. Based on the simultaneous testing, it shows that the variables of self-efficacy and creativity have a positive effect on entrepreneurial intentions by 23.4%.